(untitled) (Global Journal of Management and Business Research, 2014)
Islamic tourism is a new tourism destination in the world today. Through this tourism, religious duty was performed as well as knowledge achieved for wider dimension. By this way muslim can ensure satisfaction of Almighty Allah. The study reveals that there are huge opportunities to develop Islamic tourism in Bangladesh as it has a lot of natural beauties, Islamic heritage, cultural and archeological heritage, historic heritage, which might be potential tourism destinations. Various organizations including Organization of Islamic Conference can play vital role in this regard. The study also identifies problems in developing Islamic tourism in Bangladesh. And herewith we have provided some measures to develop this new trend of tourism to accelerate economic growth in our country.